The Influence of Professional Competence and Teacher Personality on Islamic Religious Education Learning Outcomes at SMAN 1 Mojolaban - Salma Navi'ati Kholisa Dewi; Muhammad Ja’far Nashir (JUSPI (Jurnal Sejarah Peradaban Islam), 2026)
This study aims to determine the effect of professional competence and teacher personality on student learning outcomes in Islamic Religious Education (PAI) subjects at SMA Negeri 1 Mojolaban for the 2024/2025 academic year. This research uses a quantitative approach with a descriptive method. The population in this study were all 10th-grade students, totaling 353 students, with a sample of 88 students taken using a random sampling technique. Data collection was carried out using questionnaires and documentation. Data analysis used Product Moment Correlation and multiple regression. The results showed that professional competence and teacher personality had a positive and significant effect on learning outcomes with a combined determination coefficient of 0.472. Each increase in one unit of the teacher's competency score will contribute to an increase of 0.513 in student learning outcomes.